Dosing algorithm to target a predefined AUC in patients with primary central nervous system lymphoma receiving high dose methotrexate - Joerger, Markus; Ferreri, Andrés J. M.; Krähenbühl, Stephan; Schellens, Jan H. M.; Cerny, Thomas; Zucca, Emanuele; Huitema, Alwin D. R. (British journal of clinical pharmacology, 2012)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • High dose methotrexate (HDMTX) is the most effective drug in treating primary central nervous system lymphoma (PCNSL). • While interoccasion variability of MTX elimination is moderate, interindividual variability is considerable and unpredictable. • MTX dose intensity is important in patients with PCNSL to allow for an optimal clinical outcome. • No dosing algorithm has yet been defined to individualize HDMTX dose and allow for targeting a prespecified dose intensity of the drug in patients with PCNSL. WHAT THIS STUDY ADDS • The present simulation study shows that a simple and practical dosing algorithm is able to improve the proportion of patients within a prespecified target AUCMTX. • Using this dosing algorithm, 71% of the patients received a MTX dose that was higher than the standard (500 mg m−2 over 15 min followed by 3000 mg m−2 over 3 h), while 11% of the patients received a dose that was lower than standard. AIM There is no consensus regarding optimal dosing of high dose methotrexate (HDMTX) in patients with primary CNS lymphoma. Our aim was to develop a convenient dosing algorithm to target AUCMTX in the range between 1000 and 1100 µmol l−1 h. METHODS A population covariate model from a pooled dataset of 131 patients receiving HDMTX was used to simulate concentration–time curves of 10 000 patients and test the efficacy of a dosing algorithm based on 24 h MTX plasma concentrations to target the prespecified AUCMTX. These data simulations included interindividual, interoccasion and residual unidentified variability. Patients received a total of four simulated cycles of HDMTX and adjusted MTX dosages were given for cycles two to four. RESULTS The dosing algorithm proposes MTX dose adaptations ranging from +75% in patients with MTX C24 < 0.5 µmol l−1 up to −35% in patients with MTX C24 > 12 µmol l−1. The proposed dosing algorithm resulted in a marked improvement of the proportion of patients within the AUCMTX target between 1000 and 1100 µmol l−1 h (11% with standard MTX dose, 35% with the adjusted dose) and a marked reduction of the interindividual variability of MTX exposure. CONCLUSIONS A simple and practical dosing algorithm for HDMTX has been developed based on MTX 24 h plasma concentrations, and its potential efficacy in improving the proportion of patients within a prespecified target AUCMTX and reducing the interindividual variability of MTX exposure has been shown by data simulations. The clinical benefit of this dosing algorithm should be assessed in patients with primary central nervous system lymphoma (PCNSL).